2011
DOI: 10.1097/meg.0b013e32834b8d52
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is associated with blood pressure in hypertensive and nonhypertensive individuals from the general population with normal levels of alanine aminotransferase

Abstract: In middle-aged and old adults from the general population, NAFLD is associated with an independent risk of identifying hypertension and high-normal systolic BP. Detection of NAFLD, even with normal ALT levels, should serve as an opportunity to identify metabolic and BP abnormalities and intensify lifestyle modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 0 publications
6
51
1
4
Order By: Relevance
“…A total of 39.83% of the subjects had been diagnosed with NAFLD. Our findings are inconsistent with another study that reported a lower prevalence of NAFLD (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). 11,15,16 A possible explanation for the different prevalence may originate from the characteristics of the studied populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A total of 39.83% of the subjects had been diagnosed with NAFLD. Our findings are inconsistent with another study that reported a lower prevalence of NAFLD (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). 11,15,16 A possible explanation for the different prevalence may originate from the characteristics of the studied populations.…”
Section: Discussioncontrasting
confidence: 99%
“…As Lopez‐Suarez et al . reported, approximately 50% of hypertensive patients have NAFLD . Compared to the non‐fatty liver group, the fatty liver group has a higher prevalence of hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders such as hypertension, hyperlipidemia, diabetes, gallstones, and central obesity are known risk factors for NAFLD [2,5,6]. Thyroid hormones regulate all metabolic pathways, acting on protein, carbohydrates, and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the importance of preventing and controlling this disease cannot be overemphasized. Moreover, fatty liver is closely related to metabolic syndromes, including obesity, glucose intolerance, dyslipidemia, and hypertension ( 11 ), and may be further associated with cardiovascular diseases such as atherosclerosis and coronary heart disease ( 12 ). Therefore, to ensure fl ight safety, great attention should be paid to the screening, treatment, and monitoring of pilots at risk of fatty liver.…”
Section: Discussionmentioning
confidence: 99%